First Chop Your Logos … : Socrates and the Sophists on Language, Logic and Development. Issue 2 (3rd April 2019) - McCabe, Mary Margaret
ABSTRACT: At the centre of Plato's Euthydemus lie a series of arguments in which Socrates' interlocutors, the sophists Euthydemus and Dionysodorus propose a radical account of truth ('chopped logos ') according to which there is no such thing as falsehood, and no such thing as disagreement (here 'counter-saying'). This account of truth is not directly refutable; but in response Socrates offers a revised account of 'saying' focussed on the different aspects of the verb (perfect and imperfect) to give a rich account of saying, of truth and of knowledge. I argue that Socrates' response has much to offer, notably in its amplification of the process of saying and cognition, and the development of virtue.